[PP.LB02.18] ASSOCIATION OF SOLUBLE (PRO)RENIN RECEPTOR WITH BRAIN ATROPHY IN A GENERAL POPULATION: THE OHASAMA STUDY. (September 2016) - Hirose, T.; Satoh, M.; Suzuki, H.; Hara, A.; Murakami, T.; Inoue, R.; Asayama, K.; Kikuya, M.; Metoki, H.; Terzi, F.; Totsune, K.; Takahashi, K.; et al.
Abstract : Objective: (Pro)renin receptor (PRR) is initially identified as a member of renin angiotensin system (RAS). PRR also functions as intracellular acidification (a part of V-ATPase), and cell proliferation through Wnt signaling pathway. Mutations in the PRR gene cause X-linked intellectual disability and Parkinsonism without affecting blood pressure or renal function. Soluble form of PRR (sPRR) is present in plasma and urine, and several studies have revealed the association of plasma sPRR levels with hypertension and renal function. No study, however, has investigated the association between sPRR and brain. Design and method: We obtained data on sPRR concentration and magnetic resonance imaging of the head from 350 participants (66.0% women; mean age, 66.8 years) in the general population of Ohasama, Japan. The brain was imaged at 10-mm-thick slices in the axial plane using a superconducting magnet with a main 0.5 T. Based on T1-weighted images, we calculated the brain-atrophy index (BAI) as brain parenchymal area / intracranial area * 100 (%) and used the mean BAI, which was the average of the BAIs at a basal ganglia slice and a slice at the next level. Results: Mean values were 9.9 ± 5.0 ng/mL for the sPRR and 89.3 ± 3.7 % for the mean BAI. The sPRR was significantly and inversely correlated with the mean BAI (r = -0.13, P = 0.01). After adjustments for sex, age, body mass index, current smoking status, alcohol consumption, diabetes, hyperlipidemia, history of cardiovascular disease, estimated glomerular filtration rate, the use of antihypertensive drugs, and home systolic blood pressure, the multiple linear regression model showed the significant association between the sPRR and the mean BAI (β = −0.55 [per 1 standard deviation increase in sPRR], P = 0.002). No significant interactions between sex, age (<65/ > = 65), history of cardiovascular disease, or the use of antihypertensive drugs and sPRR on the mean BAI were observed (P for interaction> = 0.08) while the largest regression coefficient of sPRR was observed in those without the use of antihypertensive drugs (β = −0.77, P = 0.0002). Conclusions: These results suggest that the sPRR levels can be inversely associated with brain atrophy in a general population.